Railway Ecology - Borda-de-Água, Luís; Barrientos, Rafael; Beja, Pedro; Pereira, Henrique Miguel (Springer Nature, 2017)
carbon footprint; environmental impacts of railways; transportation; wildlife; landscape; planning; engineering; efficiency; sustainability; biodiversity; animal casualties on rails